Posługa kapłanów w postanowieniach duszpasterskiego Synodu Archidiecezji Lwowskiej i Diecezji Łuckiej 1995-1997 - Dyduch, Jan (Prawo Kanoniczne, 2001)
Synod of the Archdiocese of Lvov, inaugurated 16th January 1995, concluded 21st January 1997, became the brilliant event in the Archdiocese’s dramatic history of the last decades. The Synod assumed the renewal of the Church of Lvov and Luck on a basis of the teaching of the Second Vatican Council and the provisions of Canon Law. The renewal of the Church life requires the renewal of priestly ministry. The Synod of Lvov turns priests’ attention to their participation in the triple mission of the Church. They take part in the teaching mission when they preach the Gospel, teach catechism and evangelize by means of mass media. They fulfil their mission of sanctification when they administer sacraments and take care ofreligious practices and piety of the faithful. While guiding God’s people and performing manifold cure of souls, they carry out their pastoral mission.